Studi Deskriptif Analisis Penanganan Remaja Akhir yang Mengalami Broken Home Melalui Konseling Pastoral di Gereja Suara Kebenaran Injil Ketapang, Kalimantan Barat - Resnita Resnita (LPPM - STT Kadesi Bogor, 2025)
Descriptive Study Analysis of Handling Late Adolescents Who Experience Broken Homes Through Pastoral Counseling at the Voice of Truth Gospel Church, Ketapang, West Kalimantan. To provide a better understanding of the role of pastoral counseling at the Voice of Truth Gospel Church in Ketapang, it can help late adolescents who experience broken homes to overcome the psychological and social impacts that arise. The research method used is a qualitative descriptive method with a case study approach. Data was collected through in-depth interviews with pastoral counselors, direct observation, and related documentation. The research results show that the pastoral counseling provided by this church includes several important stages, namely identifying problems, providing emotional and spiritual support, and providing advice based on Biblical principles. This counseling program also features support group sessions and spiritual activities aimed at strengthening youth's faith and community. This research concludes that pastoral counseling at the Voice of Truth Gospel Church in Ketapang is effective in providing support and guidance for late adolescents who experience broken homes, helping them to overcome the psychological and social impacts of their family situation. The recommendations provided include increasing training for pastoral counselors, increasing resources for counseling programs, as well as developing more structured and comprehensive intervention programs to address various aspects of the needs of late adolescents who experience broken homes.